Sosialisasi Projek Penguatan Profil Pelajar Pancasila (P5) Tema Kearifan Lokal Melalui Olahraga Tradisional Pada Siswa Skoi Kaltim - Muhammad Sukron Fauzi; Didik Cahyono; Jance J Sapulete (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this activity is to provide students with understanding and skills related to the Pancasila Student Profile Strengthening Project (P5) on the Theme of Local Wisdom in Traditional Sports for SKOI East Kalimantan Students. The advantage of this activity is completing school programs related to P5 in the independent curriculum. The method used is 1) Preparatory stage, preparing material from guidelines, PPT and Project Module Strengthening Pancasila P5 Student Profile, 2) Implementation stage, delivery of material and demonstrations related to traditional sports games, 3) Evaluation stage, sharing or discussion of values and students' understanding in implementing the socialization of the Pancasila Student Profile Strengthening Project (P5). The results of the implementation of the Community Partnership Program (PKM) were in the good and responsive category, meaning that there was an understanding of students about the Pancasila Student Profile Strengthening Project (P5). Meanwhile, students looked very enthusiastic in paying attention to the explanations conveyed by the service team with a positive response and were not ashamed ask if there is a misunderstanding in the service team's explanation. Students are very enthusiastic in terms of listening to traditional sports, which are media for introducing local wisdom values such as game sports, stilts, Bakiak, Asin Naga/Gobak Sodor, and Gasing and the monitoring results of the service team, as a whole the students have done the task given quite well. This can be seen from the results of understanding and demonstrating items from all types of traditional game sports